Factor analysis of the Scale of Prodromal Symptoms: data from the Early Detection and Intervention for the Prevention of Psychosis Program. Issue 1 (21st December 2014) - Tso, Ivy F.; Taylor, Stephan F.; Grove, Tyler B.; Niendam, Tara; Adelsheim, Steven; Auther, Andrea; Cornblatt, Barbara; Carter, Cameron S.; Calkins, Roderick; Ragland, J. Daniel; Sale, Tamara; McFarlane, William R.
Abstract: Aim: The Scale of Prodromal Symptoms (SOPS) was developed to identify individuals experiencing early signs of psychosis, a critical first step towards early intervention. Preliminary dimension reduction analyses suggested that psychosis‐risk symptoms may deviate from the traditional symptom structure of schizophrenia, but findings have been inconsistent. This study investigated the phenomenology of psychosis risk symptoms in a large sample from a multi‐site, national study using rigorous factor analysis procedure. Methods: Participants were 334 help‐seeking youth (age: 17.0 ± 3.3) from the Early Detection and Intervention for the Prevention of Psychosis Program, consisting of 203 participants at clinically higher risk (sum of P scores ≥ 7), 87 with clinically lower risk (sum of P scores < 7) and 44 in very early first‐episode psychosis (<30 days of positive symptoms). Baseline SOPS data were subjected to principal axis factoring (PAF), estimating factors based on shared variance, with Oblimin rotation. Results: PAF yielded four latent factors explaining 36.1% of total variance: positive symptoms; distress; negative symptoms; and deteriorated thought process. They showed reasonable internal consistency and good convergence validity, and were not orthogonal. Conclusions: The empirical factors of the SOPS showed similarities and notable differences compared with the existing SOPS structure. Regrouping the symptoms based on the empirical symptom dimensions may improve the diagnostic validity of the SOPS. Relative prominence of the factors and symptom frequency support early identification strategies focusing on positive symptoms and distress. Future investigation of long‐term functional implications of these symptom factors may further inform intervention strategies.